Decision Criteria in Ethical Dilemma Situations: Empirical Examples from Austrian Managers - Litschka, Michael; Suske, Michaela; Brandtweiner, Roman 1967- (2011)
This article is the result of an empirical research project analyzing the decision behaviour of Austrian managers in ethical dilemma situations. While neoclassical economic theory would suggest a pure economic rational basis for management decisions, the empirical study conducted by the authors put other concepts to a test, thereby analyzing their importance for managerial decision making: specific notions of fairness, reciprocal altruism, and commitment. After reviewing some of the theoretical literature dealing with such notions, the article shows the results of an online survey working with scenarios depicting ethical dilemma situations. By judging such scenarios the respondents showed their preference for the named concepts, though with different degrees of confirmation. The results (with all limitations of an online survey in mind) support the theoretical work on the named concepts: Fairness elements (including Rawlsian principles of justice and an understanding of fairness as conceived by a reference transaction) play a major part in management decisions in ethical dilemma situations. Also, commitment as a behaviour that sticks to rules even if personal welfare is negatively touched, and reciprocal altruism as a cooperative behaviour that expects a reciprocal beneficial action from other persons have been concepts used by Austrian managers when analyzing ethical dilemmas. The article also tries to put the results into a comparative perspective by taking into account other studies on ethical decision factors conducted with, e.g. medical doctors or journalists, and by discussing intercultural implications of business ethics.
Keywords: Sen; RECIPROCAL ALTRUISM; Management decisions; Fairness; Ethical dilemma situations; Commitment